The Effect of Environmental Concern on Green Purchase Intention Mediated by Attitude Towards Green Product, and Subjective Norm in Sensatia Botanicals Gen Z Cosmetic Users in Indonesia - Riyanto, Ricarhdus Rikky; Pangaribuan, Christian Haposan (Politeknik Siber Cerdika Internasional, 2025)
Rising environmental awareness has spurred demand for green products, yet a gap persists between concern and purchase behavior, especially among Gen Z consumers in emerging markets like Indonesia. This study investigates how environmental concern influences green purchase intention, mediated by attitude and subjective norms, using Sensatia Botanicals cosmetics as a case study. A quantitative survey of 170 Indonesian Gen Z non-buyers was analyzed via SEM-PLS to test hypotheses derived from green consumer behavior theory. Environmental concern significantly shapes attitudes toward green products (p = 0.000) but not purchase intention directly (p = 0.644). Attitude fully mediates this relationship (p = 0.000), while subjective norms show no significant mediation (p = 0.409), underscoring the dominance of personal over social factors. Marketers should prioritize attitude formation through education and product benefits over social campaigns. Future research could explore pricing strategies (e.g., dynamic pricing) and behavioral nudges to bridge the intention-action gap.